Super-linear comb-type structure emulsion polymer for oil displacement and preparation method thereof
By preparing the ultralinear comb-shaped structural emulsion polymer, the problem of insufficient shear resistance and temperature and salt resistance in low-permeability oil fields is solved, and high viscosity maintenance under high mineralization resistance and convenience in winter construction is achieved, and recovery rate is improved.
Patent Information
- Application Number
- CN202410030597.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-08
- Publication Date
- 2025-07-08
AI Technical Summary
In the prior art, HPAM materials have insufficient shear resistance and temperature and salt resistance, resulting in a decrease in viscosity of the oil-driving system and a worse fluidity ratio effect, especially during the ultra-high water content development stage of low-permeability oil fields, which is limited in the improvement of recovery.
The superlinear comb-shaped structural emulsion polymer was prepared by reverse phase emulsion polymerization using styrene-4-sulfonate and DiHMAM functional monomers. The rigid structure of benzene ring and the strong polarity of the sulfonic acid group were used to enhance the temperature and salt resistance, and the shear resistance was enhanced through the hydrophobic micro-domain association process. During the preparation process, white oil was used as the oil phase to achieve online injection.
The polymer's temperature and salt resistance and shear resistance are improved, the viscosity under high mineralization is maintained, the field equipment investment and winter construction are reduced, and the recovery rate is greatly improved in the third oil production stage of the low-permeability oil field.
Smart Images

Figure CN120271761A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oilfield development, and particularly relates to a superlinear comb-shaped emulsion polymer for oil displacement and a preparation method thereof. Background Art
[0002] In the ultra-high water cut development stage of medium and high permeability oilfields, polymer flooding, as an important part of the tertiary oil recovery technology, undertakes the main work of significantly improving the oil recovery rate. Partially hydrolyzed acrylamide polymers (HPAM), due to their large molecular weight, good thickening property, significant effects on reducing the oil-water mobility ratio and alleviating the "fingering" of the displacing agent, are widely used in the field of polymer flooding.
[0003] In low permeability oilfields, when entering the ultra-high water cut development period, the popularization of the technology for significantly improving the oil recovery rate by polymer flooding is limited by the reservoir characteristics of poor physical properties and strong heterogeneity and the fluid characteristics of high divalent cation content. The HPAM has insufficient shear resistance and temperature and salt tolerance. The pseudoplastic fluid characteristics of the polymer solution, and the entanglement points for thickening have transient properties and are in a dynamic equilibrium state, that is, high-speed shearing destroys the intermolecular interaction of the polymer, forces the molecular chains to be regularly arranged, reduces the entanglement point concentration, and leads to a decrease in the apparent viscosity. At high temperatures, the polymer molecular chains unwind, undergo relative slippage, the amide groups are hydrolyzed, and combine with M 2+ (M = Ca, Mg) to form carboxylate precipitates, the molecular chains curl, the viscosity of the oil displacement system decreases, and the effect of reducing the mobility ratio becomes worse. In view of this, it is particularly important to develop a polymer with temperature and salt tolerance and shear resistance for significantly improving the oil recovery rate in the ultra-high water cut development stage of low permeability reservoirs. Summary of the Invention
[0004] The purpose of the present invention is to provide a superlinear comb-shaped emulsion polymer for oil displacement and a preparation method thereof, so as to solve the problems that the use of HPAM materials in the prior art leads to a decrease in the viscosity of the oil displacement system and a worse effect of improving the mobility ratio due to insufficient shear resistance and temperature and salt tolerance.
[0005] On the one hand, the present invention provides a superlinear comb-shaped emulsion polymer for oil displacement, and its structure is shown as the following formula:
[0006]
[0007] Among them, x = 200 - 300, y = 20, z = 1 - 5.
[0008] On the other hand, the present application also provides a preparation method of a superlinear comb-shaped emulsion polymer for oil displacement, which is used to prepare the superlinear comb-shaped emulsion polymer for oil displacement as described in claim 1. The preparation method is characterized in that the preparation method uses sodium styrene-4-sulfonate, acrylamide and N-dodecyl-N-polyoxyethylene dodecyl acrylamide (Di Using styrene-4-sulfonate sodium, acrylamide and D i as comonomers, and under the action of a redox initiator, an inverse emulsion polymerization reaction is carried out to obtain a superlinear comb-shaped emulsion polymer for enhanced oil recovery: styrene-4-sulfonate sodium-acrylamide-D
[0009] Since the temperature and salt tolerance and shear resistance of the HPAM enhanced oil recovery agent are insufficient, the molecular chain curls or breaks, resulting in a decrease in the viscosity of the enhanced oil recovery system, and the effect of improving the mobility ratio by profile control and displacement in low-permeability oil reservoirs becomes worse. Using on-site preparation, the investment in profile control equipment is relatively large, and it is affected by the temperature in winter, making the construction difficult. In this application, styrene-4-sulfonate sodium and D i functional monomers are introduced and prepared by inverse emulsion polymerization. Under the action of shear, the reversible association process in the hydrophobic micro-region can effectively avoid the shear thinning characteristic of the polymer solution viscosity. The unique salt thickening effect is beneficial to improving the salt tolerance of the polymer. At the same time, the on-line injection characteristic of the emulsion polymer can save the cost of on-site profile control equipment and realize normal construction in winter.
[0010] In some preferred embodiments, the steps for preparing the D i HMAM are as follows:
[0011]
[0012] Adding an alkylamine and a brominated polyoxyethylene alkyl ether to carry out a nucleophilic substitution to obtain a secondary amine, and then reacting the secondary amine with acryloyl chloride to obtain the D i HMAM. Preferably, the alkylamine is a normal alkyl primary amine, and the brominated polyoxyethylene alkyl ether is obtained by the halogenation reaction of dodecyl polyoxyethylene ether (O-23), triphenylphosphine and Br2.
[0013] In some preferred embodiments, the mass fraction of the comonomers is 25%, and the molar ratio of styrene-4-sulfonate sodium, acrylamide and D i HMAM is 1:(10-15):(0.05-0.25).
[0014] In some preferred embodiments, the redox initiator includes persulfate and sodium sulfite. The addition amount of the redox initiator is 0.03-0.09% of the total molar mass of the comonomers, and the molar ratio of persulfate to sodium sulfite is 2:1. More preferably, the persulfate is any one of ammonium persulfate and potassium persulfate.
[0015] In some preferred embodiments, the aqueous phase of the inverse emulsion polymerization reaction is used to dissolve styrene-4-sulfonate sodium, acrylamide and D iDeionized aqueous solution of HMAM comonomer, the oil phase of the inverse emulsion polymerization is white oil, and the volume ratio of the deionized aqueous solution to the white oil is 1:1.
[0016] In some preferred embodiments, the inverse emulsion polymerization reaction uses a composite emulsifier, the composite emulsifier includes a first emulsifier and a second emulsifier, the first emulsifier is any one of Span 80 and Span 60, and the second emulsifier is any one of Tween 80, OP10, and Tween 60. The mass fraction of the composite emulsifier used is 4-8%.
[0017] In some preferred embodiments, the mass ratio of the first emulsifier to the second emulsifier is 1:0.05-0.25.
[0018] In some preferred embodiments, the preparation steps of the deionized aqueous solution include:
[0019] Add sodium styrene-4-sulfonate to a container, then add deionized water for dissolution. After complete dissolution, add sodium hydroxide solution to adjust the pH to neutral, and then add disodium ethylenediaminetetraacetate to complex Cu 2+ and / or Fe 2+ , to obtain an aqueous phase.
[0020] In some preferred embodiments, the steps of the inverse emulsion polymerization reaction include:
[0021] Control the polymerization temperature below 40°C. During polymerization, the aqueous phase is dispersed in the oil phase, and an emulsion is formed under stirring. Reduce the stirring speed, add an aqueous solution of ammonium persulfate, and then slowly dropwise add an aqueous solution of sodium sulfite. After the addition is completed, continue stirring under N2 protection. After the reaction is completed, obtain the product sodium styrene-4-sulfonate-acrylamide-D i HMAM emulsion polymer.
[0022] Compared with the prior art, the present application has the following advantages:
[0023] 1. The present application prepares a brand-new superlinear comb-shaped emulsion polymer flooding agent, namely sodium styrene-4-sulfonate-acrylamide-D i HMAM emulsion polymer, which has excellent temperature resistance, salt resistance and shear resistance. A displacement fluid with a concentration of 0.15% is prepared using type I simulated formation water with a salinity of 30000 mg·L -1 . At 25°C and a shear rate of 6 r / min, the viscosity of the emulsion polymer is measured to be 181.3 mPa·s, at 3500 r·min -1Under the stress of [stress value not provided], continuous shearing for 10 minutes, the viscosity is 36.4 mPa·s, and the viscosity retention rate is 78.8%. The emulsion polymer proposed in this application uses white oil as the oil phase and is prepared by inverse emulsion polymerization, which can achieve on-line injection, with a freezing point below -8°C and low construction difficulty in winter.
[0024] 2. By introducing the functional monomer sodium styrene-4-sulfonate in this application, relying on the rigid structure of the benzene ring and the strong polarity of the sulfonic acid group, the temperature and salt resistance of the copolymer can be effectively improved. On the one hand, the benzene ring structure can effectively promote the rigidity improvement of the molecular chain segments. On the other hand, the functional monomer sodium styrene-4-sulfonate has a strongly polar sulfonic acid group, which has good water solubility under high salinity. The repulsion effect of the same negatively charged sulfonic acid groups can effectively inhibit the curling of the molecular chain, and the temperature and salt resistance performance is excellent.
[0025] 3. By introducing D i HMAM functional monomer, which is a self-made double-tailed long alkyl chain macromolecular water-soluble hydrophobic monomer in the laboratory. It has a certain number of ethoxy groups between the hydrophobic unit and the unsaturated bond, which can not only complex M 2 + , but also effectively improve the water solubility of the monomer. In aqueous solution, the hydrophobic association of the double-tailed long alkyl chain spontaneously forms hydrophobic microdomains, increasing the hydrodynamic volume of the polymer and significantly increasing the viscosity of the system. Secondly, under the shear action, the reversible association process of the hydrophobic microdomains can effectively avoid the shear thinning characteristics of the polymer solution viscosity, and the unique salt thickening effect is beneficial to improving the salt resistance of the polymer.
[0026] 4. This application uses inverse emulsion polymerization to prepare a superlinear comb-shaped hydrophobic associative emulsion polymer, which has good compatibility with surfactants and can achieve on-line injection. It can not only omit the special equipment required for preparing dry powder agents but also avoid the problem of great construction difficulty in winter.
[0027] Therefore, by inverse emulsion polymerization of sodium styrene-4-sulfonate, DiHMAM functional monomer and acrylamide, the prepared superlinear comb-shaped emulsion polymer improves and optimizes the oil displacement performance of traditional polymers. Applied to the tertiary oil recovery stage of low-permeability oilfields, it is expected to achieve a significant increase in oil recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The specification drawings forming a part of the present invention are used to provide a further understanding of the present invention. The schematic embodiments and descriptions thereof of the present invention are used to explain the present invention and do not constitute an improper limitation to the present invention. In the drawings:
[0029] Figure 1 is the sodium styrene-4-sulfonate-acrylamide-D with a mass concentration of 0.15% described in Example 1 iThe variation of the apparent viscosity of the HMAM emulsion polymer with the salinity of the compound solution;
[0030] Figure 2 is the styrene-4-sodium sulfonate-acrylamide-D with a mass concentration of 0.15% described in Example 1 i The viscosity of the HMAM emulsion polymer varies with the shear time (3500 r·min -1 , 25 °C). Detailed implementation manners
[0031] The present invention will be described in detail below with reference to the drawings and in combination with embodiments. It should be noted that, without conflict, the embodiments in the present invention and the features in the embodiments can be combined with each other.
[0032] The following detailed descriptions are all exemplary descriptions, aiming to provide further detailed descriptions of the present invention. Unless otherwise specified, all technical terms adopted by the present invention have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs. The terms used in the present invention are only for describing specific implementation manners, and are not intended to limit the exemplary implementation manners according to the present invention.
[0033] Example 1
[0034] Add 15.8 g of Span 60 and 2.37 g of Tween 60 to a 250 mL beaker No. 1, weigh 106 g of white oil, and stir evenly to prepare the oil phase; add 0.06 mol of styrene-4-sodium sulfonate to a 250 mL beaker No. 2, measure 100 mL of deionized water to dissolve it, adjust it to neutral with a 7.5 mol·L-1 NaOH solution, add 0.68 mol of acrylamide and 0.0185 mol of D i HMAM, stir evenly, add 0.003 g of EDTA·2Na to complex Cu 2+ , Fe 2+ and other impurity ions, and reserve it as the water phase.
[0035] In a 500 mL three-necked flask, add the oil phase and the water phase in sequence, and the water bath temperature is 10 °C. After purging dissolved oxygen with N2 for 30 min, emulsify for 30 min at a stirring speed of 1000 r·min-1, reduce the stirring speed to 300 r·min-1, add 4.3 mL of 2% ammonium persulfate aqueous solution, and after 5 min, add 3.6 mL of 1% sodium sulfite aqueous solution dropwise. Control the dropping speed with the reaction temperature. After the dropping is completed, continue to pass N2 and keep the reaction at 50 °C for 4 h to obtain styrene-4-sodium sulfonate-acrylamide-D i HMAM emulsion.
[0036] Weigh about 10.0 g of the emulsion polymer into a 250 mL beaker. While stirring with a glass rod, slowly add 150 mL of absolute ethanol dropwise. After the addition is complete, let it stand and perform suction filtration. The solid content of the emulsion polymer is measured to be 23.7% by the weighing method. Prepare a 0.15% dispersion of the emulsion polymer with deionized water, stir evenly, and measure the apparent viscosity at 25 °C with a BrookField DV-II viscometer at a rotor speed of 6 r·min⁻¹, which is 94.6 mPa·s.
[0037] Please refer to Figure 1 and Figure 2 As shown, the styrene-4-sulfonate-sodium acrylamide-D i HMAM emulsion polymer prepared in Example 1 of the present invention uses type I simulated formation water with a salinity of 30000 mg·L -1 to prepare a displacing fluid with a concentration of 0.15%. At 25 °C and a shear rate of 6 r / min, the viscosity of the emulsion polymer is measured to be 181.3 mPa·s; under a stress of 3500 r·min -1 for 10 min of continuous shear, the viscosity is 36.4 mPa·s, and the viscosity retention rate is 78.8%. The emulsion polymer proposed in this application uses white oil as the oil phase and is prepared by inverse emulsion polymerization, which can achieve on-line injection, has a freezing point lower than -8 °C, and has little difficulty in winter construction.
[0038] Example 2
[0039] Add 15.8 g of Span 60 and 2.37 g of Tween 60 to a 250 mL beaker No. 1. Weigh 106 g of white oil and stir evenly to prepare the oil phase; add 0.06 mol of styrene-4-sulfonate-sodium to a 250 mL beaker No. 2, measure 100 mL of deionized water to dissolve it, adjust to neutral with 7.5 mol·L⁻¹ NaOH solution, add 0.68 mol of acrylamide and 0.011 mol of D i HMAM, stir evenly, add 0.003 g of EDTA·2Na to complex Cu 2+ 、Fe 2+ and other impurity ions, and reserve it as the water phase.
[0040] In a 500 mL three-necked flask, add the oil phase and the water phase in sequence, and the water bath temperature is 10 °C. After purging dissolved oxygen with N₂ for 30 min, emulsify for 30 min at a stirring speed of 1000 r·min⁻¹, then reduce the stirring speed to 300 r·min⁻¹, add 4.3 mL of 2% ammonium persulfate aqueous solution, and after 5 min, add 3.6 mL of 1% sodium sulfite aqueous solution dropwise. Control the dropping speed with the reaction temperature. After the dropping is complete, continue to purge with N₂ and keep the reaction at 50 °C for 4 h to obtain styrene-4-sulfonate-sodium acrylamide-D i HMAM emulsion.
[0041] Weigh about 10.0 g of the emulsion into a 250 mL beaker. Slowly add 150 mL of absolute ethanol dropwise under stirring with a glass rod. After the addition is completed, let it stand and filter by suction. The solid content of the emulsion polymer is measured to be 25.3% by the weighing method. The emulsion polymer is prepared into a 0.15% dispersion with deionized water, stirred evenly, and at 25 °C, the apparent viscosity is measured to be 83.6 mPa·s with a Brook Field DV-Ⅱ viscometer at a rotor speed of 6 r·min-1. According to the parameters described in Example 1, the viscosity of the emulsion polymer under high salinity (30,000 mg·L-1) is 122.7 mPa·s, and the viscosity retention rate under high shear stress is 71.5%.
[0042] Example 3
[0043] Add 15.8 g of Span 60 and 2.37 g of Tween 60 to a 250 mL beaker No. 1. Weigh 106 g of white oil and stir evenly to prepare the oil phase; add 0.06 mol of sodium styrene-4-sulfonate to a 250 mL beaker No. 2, measure 100 mL of deionized water to dissolve it, adjust to neutral with 7.5 mol·L-1 NaOH solution, add 0.68 mol of acrylamide and 0.0185 mol of DiHMAM, stir evenly, and add 0.003 g of EDTA·2Na to complex Cu 2+ 、Fe 2+ and other impurity ions for use as the aqueous phase.
[0044] In a 500 mL three-necked flask, add the oil phase and the aqueous phase in sequence, and the water bath temperature is 10 °C. After purging dissolved oxygen with N2 for 30 min, emulsify for 30 min at a stirring speed of 1000 r·min-1, reduce the stirring speed to 300 r·min-1, add 7.0 mL of 2% ammonium persulfate aqueous solution, and after 5 min, add 5.8 mL of 1% sodium sulfite aqueous solution dropwise. Control the dropping speed with the reaction temperature. After the addition is completed, continue to pass N2 and keep the reaction at 50 °C for 4 h to obtain a sodium styrene-4-sulfonate-acrylamide-D i HMAM emulsion.
[0045] Weigh about 10.0 g of the emulsion into a 250 mL beaker. Slowly add 150 mL of absolute ethanol while stirring with a glass rod. After the addition is complete, let it stand and perform suction filtration. The solid content of the emulsion polymer is measured to be 25.8% by the weighing method. Prepare a 0.15% dispersion of the emulsion polymer with deionized water, stir evenly, and measure the apparent viscosity to be 74.6 mPa·s at 25 °C using a Brook Field DV-Ⅱ viscometer with a rotor speed of 6 r·min-1. According to the parameters described in Example 1, the viscosity of the emulsion polymer under high salinity (30,000 mg·L-1) is measured to be 113.9 mPa·s, and the viscosity retention rate under high shear stress is 65.3%.
[0046] Example 4
[0047] Add 22.3 g of Span 60 and 3.34 g of Tween 60 to a 250 mL beaker No. 1. Weigh 106 g of white oil and stir evenly to prepare the oil phase; add 0.06 mol of sodium styrene-4-sulfonate to a 250 mL beaker No. 2, measure 100 mL of deionized water to dissolve it, adjust to neutral with 7.5 mol·L-1 NaOH solution, add 0.68 mol of acrylamide and 0.0185 mol of D i HMAM, stir evenly, and add 0.003 g of EDTA·2Na to complex Cu 2+ 、Fe 2+ and other impurity ions for use as the aqueous phase reserve.
[0048] In a 500 mL three-necked flask, add the oil phase and the aqueous phase in sequence, and the water bath temperature is 10 °C. After purging dissolved oxygen with N2 for 30 min, emulsify for 30 min at a stirring speed of 1000 r·min-1, then reduce the stirring speed to 300 r·min-1, add 4.3 mL of 2% ammonium persulfate aqueous solution, and after 5 min, add 3.6 mL of 1% sodium sulfite aqueous solution dropwise. Control the dropping speed with the reaction temperature. After the addition is complete, continue to pass N2 and maintain the reaction at 50 °C for 4 h to obtain a sodium styrene-4-sulfonate-acrylamide-D i HMAM emulsion.
[0049] Weigh about 10.0 g of the emulsion into a 250 mL beaker, and slowly add 150 mL of absolute ethanol dropwise under stirring with a glass rod. After the addition is completed, let it stand and then perform suction filtration. The solid content of the emulsion polymer is measured to be 24.1% by the weighing method. The emulsion polymer is prepared into a 0.15% dispersion with deionized water, stirred evenly, and at 25 °C, the apparent viscosity is measured to be 78.5 mPa·s with a Brook Field DV-II viscometer at a rotor speed of 6 r·min-1. According to the parameters described in Example 1, the viscosity of the emulsion polymer under high salinity (30,000 mg·L-1) is 137.5 mPa·s, and the viscosity retention rate under high shear stress is 73.7%.
[0050] Example 5
[0051] This example is basically the same as Example 1. The only difference is that the amounts of sodium styrene-4-sulfonate, acrylamide, and D i HMAM added are 0.06 mol, 0.4 mol, and 0.018 mol respectively;
[0052] The emulsion polymer is prepared into a 0.15% dispersion with deionized water, stirred evenly, and at 25 °C, the apparent viscosity is measured to be 57.2 mPa·s with a Brook Field DV-II viscometer at a rotor speed of 6 r·min-1. According to the parameters described in Example 1, the viscosity of the emulsion polymer under high salinity (30,000 mg·L-1) is 93.5 mPa·s, and the viscosity retention rate under high shear stress is 53.4%.
[0053] Example 6
[0054] This example is basically the same as Example 1. The only difference is that the amounts of sodium styrene-4-sulfonate, acrylamide, and D i HMAM added are 0.06 mol, 0.8 mol, and 0.018 mol respectively;
[0055] The emulsion polymer is prepared into a 0.15% dispersion with deionized water, stirred evenly, and at 25 °C, the apparent viscosity is measured to be 132.7 mPa·s with a Brook Field DV-II viscometer at a rotor speed of 6 r·min-1. According to the parameters described in Example 1, the viscosity of the emulsion polymer under high salinity (30,000 mg·L-1) is 197.3 mPa·s, and the viscosity retention rate under high shear stress is 73.2%.
[0056] Comparative Example 1
[0057] This comparative example is basically the same as Example 1. The only difference is that D iHMAM only uses sodium styrene-4-sulfonate and acrylamide as copolymerization monomers to carry out inverse emulsion polymerization reaction, and the apparent viscosity of the obtained emulsion copolymer is 31.8. According to the parameters described in Example 1, the viscosity of the emulsion polymer under high salinity (30000 mg·L-1) is measured to be 6.9 mPa·s, and the viscosity retention rate under high shear stress is 40.7%.
[0058] As is known by common technical knowledge, the present invention can be implemented by other embodiments that do not depart from its spiritual essence or essential features. Therefore, the above-disclosed embodiments are illustrative in all aspects and not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are encompassed by the present invention.
Claims
1. A superlinear comb-shaped emulsion polymer for enhanced oil recovery, with its structure shown as follows: Among them, x = 200 - 300, y = 20, z = 1 - 5.
2. A preparation method of a superlinear comb-shaped emulsion polymer for enhanced oil recovery, which is used to prepare the superlinear comb-shaped emulsion polymer for enhanced oil recovery as described in claim 1, and is characterized in that, The preparation method uses three raw materials, namely sodium styrene-4-sulfonate, acrylamide, and DiHMAM, as comonomers, and carries out an inverse emulsion polymerization reaction under the action of a redox initiator to obtain a superlinear comb-shaped structure emulsion polymer for enhanced oil recovery: sodium styrene-4-sulfonate-acrylamide-D i HMAM emulsion copolymer.
3. The preparation method of a superlinear comb-shaped structure emulsion polymer for oil displacement according to claim 2, characterized in that, Preparing the D i The steps of HMAM include: An alkylamine is added and undergoes nucleophilic substitution with a brominated polyoxyethylene alkyl ether to obtain a secondary amine, and then the secondary amine is reacted with acryloyl chloride to obtain the D i HMAM.
4. The preparation method of a superlinear comb-shaped structure emulsion polymer for oil displacement according to claim 2, characterized in that, The sodium styrene-4-sulfonate, the acrylamide, and the D i The molar ratio of HMAM is 1:(10 to 15):(0.05 to 0.25).
5. The preparation method of a superlinear comb-shaped emulsion polymer for oil displacement according to claim 2, characterized in that, The redox initiator includes persulfate and sodium sulfite, and the addition amount of the redox initiator is 0.03 - 0.09% of the total molar mass of the comonomers. The molar ratio of the persulfate to the sodium sulfite is 2:
1.
6. The preparation method of a superlinear comb-shaped emulsion polymer for oil displacement according to claim 2, characterized in that, The aqueous phase of the inverse emulsion polymerization reaction is a deionized aqueous solution for dissolving sodium styrene-4-sulfonate, acrylamide, and D i HMAM comonomer. The oil phase of the inverse emulsion polymerization is white oil, and the volume ratio of the deionized aqueous solution to the white oil is 1:
1.
7. The preparation method of a superlinear comb-shaped structure emulsion polymer for oil displacement according to claim 2, wherein The inverse emulsion polymerization reaction uses a composite emulsifier, which includes a first emulsifier and a second emulsifier. The first emulsifier is any one of Span 80 and Span 60, and the second emulsifier is any one of Tween 80, OP10, and Tween 60.
8. The preparation method of a superlinear comb-shaped emulsion polymer for oil displacement according to claim 7, characterized in that The mass ratio of the first emulsifier to the second emulsifier is 1:(0.05 - 0.25).
9. The preparation method of a superlinear comb-shaped emulsion polymer for oil displacement according to claim 6, characterized in that, The preparation steps of the deionized aqueous solution include: Add sodium styrene-4-sulfonate to a container, then add deionized water for dissolution. After complete dissolution, add sodium hydroxide solution to adjust the pH to neutral, and then add disodium ethylenediaminetetraacetate to complex Cu 2+ and / or Fe 2+ , to obtain an aqueous phase.
10. The preparation method of a superlinear comb-shaped emulsion polymer for oil displacement according to claim 2, characterized in that, The steps of the inverse emulsion polymerization reaction include: Control the polymerization temperature below 40 °C. During polymerization, the aqueous phase is dispersed in the oil phase to form an emulsion under stirring. Then, reduce the stirring speed and add an aqueous solution of ammonium persulfate. Subsequently, slowly dropwise add an aqueous solution of sodium sulfite. After the dropping is completed, continue stirring under N2 protection. After the reaction is completed, the product sodium styrene-4-sulfonate-acrylamide-D i HMAM emulsion polymer is obtained.